Penerapan Metode FIFO Pada Sistem Informasi Persediaan Barang - Sifa Fauziah; . Ratnawati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Inventory system is a process to determine and manage goods that function to obtain an information about the stock of goods that exist. In this case the authors focus on controlling existing pipeline inventory at PT Fivalco Indonesia. The greater the amount of inventory of goods owned by PT Fivalco Indonesia, now the data processing in PT Fivalco Indonesia there are often problems in terms of availability of stock items such as stock shortages or excess stock even the difference in stock. Recognizing that the growing company will be more and more data is processed, then PT Fivalco Indonesia requires application programs for inventory. Therefore it is needed a inventory information system in PT Fivalco Indonesia that can determine the amount of inventory in covering all orders from consumers and also an information system that can support all activities on inventory management goods. Overcome the existing problems, the writer tries to apply inventory information system with FIFO method using Microsoft Visual Basic and MySQL database so that users work in inventory management to be efficient and effective and will facilitate the sales department to demand goods out and demand of goods in company need to check directly to the warehouse to find out information about the stock of goods.